(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Present paper is an attempt to study Computer Phobia among secondary school teachers, because use of computer for teaching influence the students learning as well as make teaching process effective. The study is aim to analyze the difference in Computer Phobia among secondary school Teachers with respect to their Gender, stream and educational Qualification. 400 secondary school teachers were selected by purposive sampling technique via administered Computer Phobia Scale developed by Rajashekar and Raja (2010) from senior secondary school of Hisar, Jind and Fatehabad districts of Haryana. The result revealed that most of teachers reported neutral computer phobia, whereas only 2.25 teacher have higher level of Computer Phobia. Further, it is found a significant difference in computer phobia among teachers with the reference of gender and stream, whereas, there is no significance difference in computer phobia found among teachers with the reference of their level of qualification.